Prevalence and predictors of post-abortion modern contraceptive utilization among reproductive age women in Ethiopia - Tadele Biresaw Belachew; Wubshet Debebe Negash; Desale Bihonegn Asmamaw; Samrawit Mihret Fetene; Banchlay Addis; Tsegaw Amare Baykeda; Atitegeb Abera Kidie; Abel Endawkie; Alebachew Ferede Zegeye; Tadesse Tarik Tamir; Elsa Awoke Fentie; Sisay Maru Wubante (Scientific Reports, 2023)
Abstract The development of a post-abortion family plan is an integral part of comprehensive abortion care. In spite of this, it received insufficient attention as a means of breaking the cycle of repeated abortions, unintended pregnancies, and maternal deaths resulting from abortion. Therefore, this study examined post abortion modern contraceptive utilization among Ethiopian women as well as associated factors. The study was based on secondary data analysis of the Ethiopian Demographic and Health Survey 2016 data. A total weighted sample of 1236 reproductive age women was included. A multilevel mixed-effect binary logistic regression model was fitted to identify the significant associated factors of post abortion contraceptive use. Statistical significance was determined using Adjusted Odds Ratio (AOR) with 95% confidence interval. Overall prevalence of post abortion contraceptive use was observed to be 25.6% (95% CI: 23.24, 28.12). Women's age 15–24 (AOR = 2.34; 95% CI: 1.11, 4.93), and 25–34 (AOR = 1.94; 95% CI: 1.27, 2.98), married women (AOR = 2.6; 95% CI: 1.43, 4.96), women who had 1–4 (AOR = 4.13; 95% CI: 1.79, 9.57) and ≥ 5 number of children (AOR = 8.80; 95% CI: 3.30, 13.49), Being in metropolitan region (AOR = 9.14; 95% CI: 1.79, 12.48), women being in urban area (AOR = 1.85; 95% CI: 1.32, 2.24), and community media exposure (AOR = 1.75; 95% CI: 1.11, 3.56) were associated with post abortion modern contraceptive use. Post abortion modern contraceptive use in this study was low. Women age, current marital status, number of living children, residency, community media exposure, and region were significantly associated with post abortion modern contraceptive utilization. Therefore, it is better to provide ongoing health information about post-abortion family planning and its benefits, especially for people who live in rural and small peripheral regions, and public health policymakers should take both individual and community level factors into account when designing family planning programmes.